2018
DOI: 10.1039/c8cy01174e
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of cyclic esters, epoxides and anhydrides: evidence of the dual role of the monomers in the reaction mixture

Abstract: A block copolyester derived from ROCOP of CHO/SA followed by ROP of ε-CL was obtained from the mixture of monomers. The lactone comonomer acts as an endogen cocatalyst during the SA/CHO ROCOP step and as a monomer during ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 71 publications
3
29
0
Order By: Relevance
“…Recently we showed that Cr(III) or Al(III) catalyst systems follow the same mechanism and yielded block polyesters 23,28 . Other researchers have successfully applied the same switchable polymerization method to di-zinc 20 , di-aluminium 29 and transition metal 30 catalysts. A requirement for successful catalysis is that the ROCOP cycles yield highly alternating polyesters, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we showed that Cr(III) or Al(III) catalyst systems follow the same mechanism and yielded block polyesters 23,28 . Other researchers have successfully applied the same switchable polymerization method to di-zinc 20 , di-aluminium 29 and transition metal 30 catalysts. A requirement for successful catalysis is that the ROCOP cycles yield highly alternating polyesters, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One common strategy for tuning the polymer properties such as glass transition temperature ( T g ) is to incorporate additional monomers to form block or random copolymers [ 51 , 52 , 53 , 54 ]. Given the versatility of the current zinc catalysts for various epoxides and anhydrides, we were interested to see if terpolymerization could be achieved and how it could affect the properties of the resulting terpolymers.…”
Section: Resultsmentioning
confidence: 99%
“…The highest performances of the latter were attributed to possible cooperative effects between the two metal centers in close proximity due to the shorter backbone. The complex also proved as an efficient catalyst for the homo-and copolymerization of other cyclic esters (L-LA, ε-CL and β-BL), epoxides and anhydrides [133].…”
Section: Aluminummentioning
confidence: 99%